Comprehensive analysis of m5C-Related lncRNAs in the prognosis and immune landscape of hepatocellular carcinoma - Lu, Qian; Liu, Lianyu; Wang, Shuai; Zhang, Qi; Li, Li (Frontiers in Genetics, 2022)
5-methyladenosine methylation (m5C) is one type of epigenetic modifications involved in the progression of various cancers. In order to investigate the role of m5C-related lncRNAs in prognosis and immune cell infiltration in Hepatocellular Carcinoma (HCC), we obtained patients’ clinical information and transcriptome data of HCC from The Cancer Genome Atlas (TCGA) database and explored m5C-related lncRNAs with prognostic value. Pearson correlation analysis was applied to construct a m5C-related lncRNAs-mRNAs co-expression network. Univariate Cox analysis, least absolute shrinkage and selection operator (LASSO), and multivariate Cox analysis were used to establish a m5C-related lncRNA prognostic risk model. The model was verified using Kaplan–Meier analysis, principal component analysis, univariate and multivariate Cox analysis. We validated the expression of the m5C-related lncRNAs in HCC tissues and different cell lines. Combining the risk score and clinicopathological features, a nomogram was established for predicting the overall survival (OS) of HCC patients. Furthermore, GSEA analysis revealed that some tumor associated pathways were significantly enriched in the high-risk group. Immune cell infiltration analysis showed that the level of Treg cells, neutrophils, and M2 macrophages was higher in the high-risk group. In addition, patients with high tumor mutation burden (TMB) had the worse OS than those with low-TMB. Immune checkpoint level and chemotherapeutic agent sensibility were also assessed. In conclusion, m5C-related lncRNAs played a critical role in predicting the prognosis of patients with HCC and may serve as new therapeutic targets for HCC patients.